A Narrative Enrichment Programme in literacy development of Afrikaans speaking Grade 3 learners in monolingual rural schools - Brand, Irene (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.